Aspekty prawne i społeczne nowelizacji wieku pełnoletności wprowadzonej w Japonii 1 kwietnia 2022 r. - Jelonek, Barbara (Studia Prawa Publicznego, 2022)
On 1 April 2022, an amendment to the Civil Code (Jap. Minpō) entered into force in Japan to change the deﬁnition of the age of majority. For the ﬁrst time in that country’s history, the threshold for reaching the age of majority has been changed. The article discusses the legal provisions that have been revised in connection with the amendment to the Japanese Civil Code and the social challenges that accompany this legal change. The previous age of majority had been in force in Japan since 1876. The aim of the 2018 amendments to the Japanese Constitution and Electoral Law was to lower the active age of voting rights from 20 to 18, and thus to involve citizens at an earlier age in the political, social and economic life of the country. On the other hand, the change of the Civil Code and the introduction of the age of majority from 20 to 18 on 1 April 2022 aimed to increase the social participation of young people by including 18- and 19-year-olds in deciding about their own lives, about their academic and professional paths, starting a family and concluding civil law contracts and taking responsibility for their decisions and dealing with the consequences arising from them. This legal change leads to the fact that citizens who now enter adulthood earlier than their peers in previous years in Japan will now have more economic freedom, but at the same time, they must bear in mind the full range of legal consequences and responsibility for their actions. The legal amendment to the age of majority discussed in the text, as intended by the Japanese legislator, aims to create the conditions for young Japanese people to make economically and politically informed decisions, thereby preparing young citizens more consciously for the challenges related to their participation in the economic life of this country.